The molecular dimension of microbial species: 2. Synechococcus strains representative of putative ecotypes inhabiting different depths in the Mushroom Spring microbial mat exhibit different adaptive and acclimative responses to light - Nowack, Shane; Olsen, Millie T.; Schaible, George A.; Becraft, Eric D.; Shen, Gaozhong; Klapper, Isaac; Bryant, Donald A.; Ward, David M. (Frontiers in Microbiology, 2015)
Closely related strains of thermophilic Synechococcus were cultivated from the microbial mats found in the effluent channels of Mushroom Spring, Yellowstone National Park (YNP). These strains have identical or nearly identical 16S rRNA sequences but are representative of separate, predicted putative ecotype populations, which were identified by using the more highly resolving psaA locus and which predominate at different vertical positions within the 1-mm-thick upper-green layer of the mat. Pyrosequencing confirmed that each strain contained a single, predominant psaA genotype. Strains differed in growth rate as a function of irradiance. A strain with a psaA genotype corresponding to a predicted putative ecotype that predominates near the mat surface grew fastest at high irradiances, whereas strains with psaA genotypes representative of predominant subsurface populations grew faster at low irradiance and exhibited greater sensitivity to abrupt shifts to high light. The high-light-adapted and low-light-adapted strains also exhibited differences in pigment content and the composition of the photosynthetic apparatus (photosystem ratio) when grown under different light intensities. Cells representative of the different strains had similar morphologies under low-light conditions, but under high-light conditions, cells of low-light-adapted strains became elongated and formed short chains of cells. Collectively, the results presented here are consistent with the hypothesis that closely related, but distinct, ecological species of Synechococcus occupy different light niches in the Mushroom Spring microbial mat and acclimate differently to changing light environments.